Interpretação paleogeográfica de sítios arqueológicos em solos arenosos: o caso do sítio MT1 na bacia do médio rio Tocantins (TO) - Lima, Fernanda Rodrigues de (2015)
From Geoarchaeology, discipline that results from the interface between Archaeology and Geosciences, with an emphasis on Physical Geography and Paleogeography, as well as the formation process of archaeological record, this research analyzed the natural factors that conditioned archaeological site formation of Miracema do Tocantins 1 (MT1), currently, under Cerrado domain. The site, seated on sandy sediments on the left bank, of the middle course of Tocantins river, Miracema do Tocantins (TO), has been occupied since the beginning of the Holocene, just over 10.000 years BP, with intervals of no occupation. This study tested the idea that, the geological substrate of the site was a member of a supposed Quaternary paleodunes field in the region, now mischaracterized by Cerrado coverage and soil that it developed. The study started by the environmental characterization of the area, with emphasis on compilation and adaptation of geology, pedology and geomorphology information, followed by data collection in the field, which included the observation of the landscape, the exposure and description of geopedological substrate, collecting material for physical, pedostratigraphics and geochronological analysis, and the observation of the sedimentary structures, to identify the site substrate and post-depositional processes related to pedogenesis. The studies and analysis of pedologic materials indicated that the bedrock’s natures is sedimentary petrographic, dated from the Lower Carboniferous, associated with a wet environment sedimentation, of marine and fluvial facies; with absence of cross stratification, typical of wind dunes; and the sandy pedologic material exhibits textural homogeneity with medium sand fraction domain, is poorly sorted, of subrounded grains, subangular and high sphericity, but asymmetrically positive pattern. The soil morphology and composition exhibited progressive pedogenetic process without lithological or erosive discordance, with grains exposed to solar radiation at about 9.100 years and 4.870 years BP, according to OSL dating. In conclusion, the sandy material of the soil site comes from the change of the source material from rocks inherited from Carboniferous formation, giving rise to Quartzarenic Neosol, which was reworked during the Holocene by gravity displacement (colluvial deposition) and low-power wind process (not formed dunes), covering the layers of archaeological occupation dated from 10.530 years BP and 5.980 years BP.